2013
DOI: 10.1016/j.fertnstert.2013.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation patterns in women with acquired hypoactive sexual desire disorder and women with normal sexual function: a cross-sectional pilot study

Abstract: Objective To examine and compare brain activation patterns of premenopausal women with normal sexual function and those with hypoactive sexual desire disorder (HSDD) during viewing of validated sexually explicit film clips. Design Cross-sectional pilot study. Setting University-based clinical research center. Patient(s) Premenopausal women. Intervention(s) None. Main Outcome Measure(s) Areas of brain activation during viewing of sexually explicit film clips. Result(s) Women with normal sexual funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 60 publications
(71 reference statements)
1
30
0
1
Order By: Relevance
“…15 Regardless of the disorder's label, 15,16 if a woman suffers from prolonged loss of sexual desire that causes her distress and cannot be explained by problematic relationships, stressors, or medical conditions, then it is considered to be a disorder of reward processing for sex, and as such is hypothetically mediated by inefficient information processing in reward circuits. [1][2][3][4][5][6] Disorder of Sexual Interest and Desire, or of Arousal?…”
Section: Reward Processing As a Symptom Dimension In Psychiatric Disomentioning
confidence: 99%
See 2 more Smart Citations
“…15 Regardless of the disorder's label, 15,16 if a woman suffers from prolonged loss of sexual desire that causes her distress and cannot be explained by problematic relationships, stressors, or medical conditions, then it is considered to be a disorder of reward processing for sex, and as such is hypothetically mediated by inefficient information processing in reward circuits. [1][2][3][4][5][6] Disorder of Sexual Interest and Desire, or of Arousal?…”
Section: Reward Processing As a Symptom Dimension In Psychiatric Disomentioning
confidence: 99%
“…3,4,8,18 However, until recently, primary disorders of interest in and desire for sex have not been well recognized. [1][2][3][4][5][6] Recent changes in diagnostic criteria for sexual disorders have arguably made it even more difficult to reach a primary diagnosis of loss of interest in and desire for sex. 15 Confusion exists because some diagnostic systems now merge disorders of interest and desire in women with disorders of arousal, while other diagnostic systems keep them separate.…”
Section: Reward Processing As a Symptom Dimension In Psychiatric Disomentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, evidence from laboratories (including fMRI studies) around the world supporting a mind/body integration becomes more abundant with each year that passes [8][9][10]. For example, a very recent fMRI study demonstrated how neurons in the prefrontal cortex contribute to cognitive and emotional processes and in doing so may both enhance and disrupt sexual desire and function [7].…”
mentioning
confidence: 99%
“…Although the underlying pathophysiology is not completely understood, functional Magnetic resonance imaging (MRI) studies reveal persistent changes in brain activation and deactivation patterns in women with HSDD, compared with women with no history of HSDD. [11][12][13] Thus, treatment options that include pharmacotherapy to correct or counteract these alterations in brain function are likely to be effective in treating HSDD or able to serve in a combined pharmacological and psychological approach. Currently, there are no approved pharmacotherapies for HSDD in the USA.…”
mentioning
confidence: 99%